The BCS glossary of ICT and computing terms (Harlow, England, 2004)
The world of computers is fast-moving and filled with jargon, so keeping up-to-date with the terminology can be daunting. The eleventh edition of this well-established authoritative glossary assumes no previous computing knowledge and uses simple language and numerous illustrations to guide the reader. The glossary explains over 3000 computing terms. Its unique structure links related terms together in such a way that the definitions are always placed in context to help understanding.
Keywords: Electronic data processing,Computers,Information technology; Dictionaries,Dictionaries,Dictionaries